A DISCOURSE ANALYSIS ON POLITENESS USED BY MR. BOND IN KORAN PENDIDIKAN NEWSPAPER - Dian Luthfihayati (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
In communication, people express their thought with or without words. We may understand what they want by listening to their words carefully, but it cannot be denied that it would be better for us if we also could read their thought by their gestures. Politeness is the expression of the speaker’s intention to mitigate face threats carried by certain face threatening acts toward another (Mills, 2003). Being polite therefore consist of attempting to safe for another. Politeness theory states that some speech acts threaten other’s face needs. The purpose of this paper is to give new source by applying a well known Brown and Levinson’s model (1978 and revised in 1987). This study using descriptive  qualitative research since this study describe the kinds of politeness that used by Mr. Bonds. The results of this study are Mr. Bond using negative and positive politeness in his speech based on the situation and condition. The politeness that more appear in his speech is negative politeness. Because he often in uncomfortable situation and feel angry. Keywords: Politeness, Koran Pendidikan